A Multi-Objective Model for Job Shop Flexible Scheduling Problem by Considering The Flexibility in Sequencing and Constraints of Activity in Uncertainty Condition - Shojaei, Arsalan; Jafari, Davood; Khalaj, Mehran (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
The current research aims to develop a multi-objective model for the flexible job shop scheduling problem (FJSP) by incorporating flexibility in sequencing and activity constraints under conditions of uncertainty. To achieve this, a comprehensive study was conducted to identify research gaps. Based on these gaps, the assumptions and research objectives were formulated. The proposed multi-objective mathematical programming model (MOMPM) focuses on three primary goals: minimizing makespan, minimizing labor workload, and minimizing weighted delays. The contributions of this study include flexibility in sequencing, activity constraints, uncertainty in processing times, and sequence-dependent setup times. The model is solved using a multi-objective genetic algorithm (MOGA), and the results indicate that flexibility in activities does not lead to suboptimal solutions, nor do activity constraints. However, uncertainty in processing times can adversely affect the optimal solutions across all objectives.